Het gezicht van dementie in de media - Diesfeldt, Han F.A. (Tijdschrift voor Gerontologie en Geriatrie, 2013)
bespreking recente onderzoeksliteratuur Kessler, E.& Schwender, C. (2012). Giving dementia a face? The portrayal of older people with dementia in German weekly news magazines between the years 2000 and 2009. The Journals of Gerontology, Series B: Psychological Sciences and Social Sciences, 67, 261-270.